THE TRANSITION OF TASHKENT PROPERTY INTO THE HANDSOFABDULLAH BAHADUR KHAN - Kimsanova Rukhshona Khayrullayevna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This study examines the process of the incorporation of Tashkent into the domain of Abdullakhan II from a historical and political perspective. It highlights dynastic conflicts within the Shaybanid state, particularly the confrontation with Navruz Ahmad Khan (Baroq Khan) and his descendants, as key factors. The military campaign of 1582 and the defeat of Bobo Sultan are evaluated as decisive events in subordinating Tashkent to central authority. The study concludes that this process played a crucial role in strengthening political centralization and overcoming territorial fragmentation in Transoxiana.